The Alliance Between Politics and Philosophy with Regard to the Threats of the XXI Century - Poghosyan, Will (Տիգրան Մեծ)
The alliance between politics and philosophy pursues the objectto change the world as public or social life. The life implies various degrees of quality, and suggests existence regarded as a desirable condition: life, liberty, and the pursuit of happiness. This is the main point of the Declaration of Independence (July 4, 1776). We have here a whole philosophy of politics referring to Plato’s doctrine of the practical influence of philosophy on the state power to change the world (Plato, 1971, Rp. V 473d, VI 501e, VII 540d). The philosophy of politics holds life, liberty, and the pursuit of happiness to be unalienable rights and just so lays down the basic human rights as the principles of the political law, public law. The form of government which secures these rights is called democracy. America is no longer the ruler of her own spirit. In Armenia and Russia, there is instituted now timocracy, a form of government in which love of honor is the ruling principle (timē honor + krateein to rule). There exist here public law apart from human rights. The task of the philosophy of politics is to secure democracy in the United States of America and to carry out the transition from timocracy to democracy in the Republic of Armenia and the Russian Federation.
Keywords: Political Philosophy